Chronic schistosome infection leads to modulation of granuloma formation and systemic immune suppression - Lundy, Steven K.; Lukacs, Nicholas W. (Frontiers in Immunology, 2013)
Schistosome worms have been infecting humans for millennia, but it is only in the last half century that we have begun to understand the complexities of this inter-relationship. As our sophistication about the inner workings of every aspect of the immune system has increased, it has also become obvious that schistosome infections have broad ranging effects on nearly all of the innate and adaptive immune response mechanisms. Selective pressures on both the worms and their hosts, has no doubt led to co-evolution of protective mechanisms, particularly those that favor granuloma formation around schistosome eggs and immune suppression during chronic infection. The immune modulatory effects that chronic schistosome infection and egg deposition elicit have been intensely studied, not only because of their major implications to public health issues, but also due to the emerging evidence that schistosome infection may protect humans from severe allergies and autoimmunity. Mouse models of schistosome infection have been extremely valuable for studying immune modulation and regulation, and in the discovery of novel aspects of immunity. A progression of immune reactions occurs during granuloma formation ranging from innate inflammation, to activation of each branch of adaptive immune response, and culminating in systemic immune suppression and granuloma fibrosis. Although molecular factors from schistosome eggs have been identified as mediators of immune modulation and suppressive functions of T and B cells, much work is still needed to define the mechanisms of the immune alteration and determine whether therapies for asthma or autoimmunity could be developed from these pathways.